Anxiety Levels Analysis Based on Confidence and Emotion Regulation in Basketball Athletes - Rizka Fitrian Rimadani; Yusuf Hidayat; Tri Martini (Universitas Negeri Semarang, 2025)
This study aimed to examine the relationship between self-confidence and emotion regulation and competitive anxiety among female basketball athletes. A quantitative correlation research design was used by involving 53 female athletes participating in the Bandung Student League, who were selected through purposive sampling. Data were collected using questionnaires of confidence, emotion regulation, and competitive anxiety and analyzed using multiple linear regression. The results showed that confidence and emotion regulation were significantly and negatively associated with competitive anxiety (R² = 0.54 p < 0.05), suggesting that both variables contributed substantially to explaining the variation in athletes’ anxiety levels. The R2 value in this study was 0.540 or 54%, suggesting that anxiety variance can be explained by confidence and emotion regulation. This means that there are 46% of other factors that affect anxiety besides self-confidence and emotion regulation. Athletes with higher levels of confidence and better emotion regulation tend to experience lower levels of anxiety during competitive situations. These findings suggest that psychological factors, especially confidence and emotion regulation, play an important role in reducing competitive anxiety among female basketball athletes.